Standardization of an antimicrobial resistance surveillance network through data management - Kim, Hyunji; Park, Jeong Su; Kim, Dokyun; Kim, Hee Jung; Shin, Jeong Hwan; Kim, Young Ah; Uh, Young; Kim, Soo Hyun; Shin, Jong Hee; Jeong, Seok Hoon; Park, Kyoung Un (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe rapid spread of COVID-19 worldwide within 2 months demonstrated the vulnerability of the world’s population to infectious diseases. In 2015, the Global Antimicrobial Resistance and Use Surveillance System (GLASS) was launched to combat antimicrobial resistance (AMR). However, there has been no comprehensive assessment of the decade-long global battle against AMR based on GLASS data.MethodsSouth Korea established Kor-GLASS (Korean-GLASS) to proactively monitor data quality and enable international collaborations. A unique feature of Kor-GLASS is the quality control center (QCC), which uses network hubs and ensures standardized, high-quality data through interlaboratory proficiency testing (IPT) and external quality assessment (EQA). In addition, the QCC multifaceted endeavors for integrated data quality management.ResultsSince 2020, high-quality AMR data have indicated fluctuating antibiotic resistance rates in South Korea. This trend does not align with the decrease in antibiotic usage seen in humans but coincides with non-human antibiotic sales, indicating a need for greater monitoring of non-human antibiotic resistance. Comprehensive and robust management taking account of the intricate interplay among humans, animals, and the environment is essential. Kor-GLASS has been expanded into a “One Health” multiagency collaborative initiative.DiscussionAlthough a standardized solution is not suitable for all countries, it must align with the local context and international standards. A centralized top-down management structure such as that of the QCC is essential to ensure continuous data quality coordination. Sustained efforts and surveillance systems are crucial for monitoring and managing AMR and safeguarding human health.